A eficácia da instrução pragmática : o ensino e a aprendizagem de pedidos entre aprendizes de inglês - Barros, Angélica Coelho (2016)
Pragmatic Studies show that linguistic competence alone is not enough for learners of a foreign language to be able to suit utterances to different communicative contexts. Authors such as Brown and Levinson (1978) and Trosborg (1994) stated that the lack or inappropriate use of pragmatic principles can generate negative conclusions in relation to the speaker and / or listener. These can be misinterpreted and misjudged rude, unfeeling, uncooperative, disrespectful, among others, during specific circumstances of communication. This may occur with significant frequency among individuals from different communities, therefore, English learners as a foreign language or second language need to be significantly more aware of the function of speech and the degree of linguistic politeness in face to face interactions. However, even though many studies suggest that the teaching and learning of a foreign language must include a pragmatic instruction in order for learners to improve their communicative competence, many approaches of regular schools and of language teaching centers, still gives priority to communicative competence development. Studies such as Kasper and Schmidt (1996) and Bardovi-Härlig (2001) argue that pragmatic instruction, especially those aimed at the mitigation of speech acts are important to complement the communicative competence of learners. Thus, the objective of this study is to propose the improvement of the communicative competence of 29 advanced learners of English as a foreign language aged between 18 and 30 years. To do this, a pragmatic instruction was used and aimed at the teaching and learning of 11 politeness strategies. This study is based on the theory of speech acts of Austin (1962) Searle (1969, 1975) on the concept of politeness of Brown and Levinson (1978) and on the classification of request strategies of Trosborg (1994). The results of this research showed that after the pragmatic instruction apprentices showed a greater use of politeness strategies and made use of strategies that were not observed in the pre-test results. Thus, a significant increase of strategies in the performance of the apprentices was observed in the posttest when compared to the pretest results.